Allelopathic effects of jack bean leaf aqueous extract on safflower cultures - Seabra Júnior, Edward; Dal-Pozzo, Daniel Marcos; Feiden, Armin; Ferreira Santos, Reginaldo; Kazue Tokura, Luciene (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2018)
This study verified the allelopathic influence of jack bean leaves (Canavalia ensiformis) on safflower cultures (Carthamus tinctorius), applied at different concentrations. Ten safflower genotypes were seeded in 20 containers, and a concentrate was prepared with jack bean leaves, crushed with water to make the extract. Five treatments were performed with four replicates, and this extract was applied at concentrations of 0%, 25%, 50%, 75% and 100%. The parameters were germination speed, percentage of germination, dry and fresh mass, leaf and root size. The jack beans influenced each evaluated treatment differently, presenting, at some times, neutral characteristics, inhibitory characteristics, or stimulating characteristics, varying according to the percentage of extract that was applied.